2022
DOI: 10.3390/ani12151908
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Contagious Yawning in Humans

Abstract: Contagious yawning, or the reflexive tendency to yawn following the detection of yawning in others, is well-documented among humans and a growing number of social vertebrates. While the most common form of yawn contagion occurs between conspecifics, some non-human animals in captivity have been reported to yawn in response to yawns from human handlers/caregivers. The current research sought to provide the first formal investigation of whether people yawn contagiously in response to yawns from non-human animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 83 publications
3
14
0
Order By: Relevance
“…This is the first evidence of changes in cognitive performance induced by the simple observation of others’ yawns. Recently, the study has been replicated basically finding the same results (Gallup and Wozny 2022 ). Although the constraints on generalization make direct comparisons difficult, our data on the immediate effect of spontaneous yawning on subsequent behaviors and the tendency of the observers to replicate others’ yawns (Prediction 5 supported, Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This is the first evidence of changes in cognitive performance induced by the simple observation of others’ yawns. Recently, the study has been replicated basically finding the same results (Gallup and Wozny 2022 ). Although the constraints on generalization make direct comparisons difficult, our data on the immediate effect of spontaneous yawning on subsequent behaviors and the tendency of the observers to replicate others’ yawns (Prediction 5 supported, Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Yawn contagion has been extensively documented in human (Norscia and Palagi 2011 ; Palagi et al 2020 ; Provine and Hamernik, 1986 ; Provine, 2005 ) and nonhuman animals (birds, Miller et al 2012 ; social carnivores, Romero et al 2014 ; Casetta et al 2021 ; Ake and Kutsukake 2023 ; monkeys, Palagi et al 2009 ; Valdivieso-Cortadella et al 2023 ; great apes, Campbell and Cox 2019 ; Demuru and Palagi 2012 ) with some exceptions (birds, Gallup et al 2022 ; lowland gorillas, Palagi et al 2019a , b ). It has been recently demonstrated that yawn contagion can also occur between different species (Gallup and Wozny 2022 ; Pedruzzi et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an independent study in EBS was created alongside the minor, which provides students the opportunity to gain hands-on evolutionarily-based research experience as undergraduates. Notably, the first time this course was offered (Spring 2022) resulted in a peer-reviewed publication that was co-authored by a psychology major minoring in EBS (Gallup & Wozny, 2022).…”
Section: Evos Journal: the Journal Of The Evolutionary Studies Consor...mentioning
confidence: 99%
“…One of these theories (i) focuses on affective communication [ 30 ], where humans can read the inner state-related information in dog barks [ 15 ], and mostly the perceived negative emotions elicit nuisance in the receivers. This mechanism could be explained on the basis of inter-specific empathy [ 34 ], which has an important role in dog-human interactions [ 19 ]. The other explanation (ii) is that specific barks have a strong attention-eliciting effect [ 32 ] and just like baby cries, in case of prolonged exposure they may elicit stress and eventually frustration and anger from the listeners [ 35 ].…”
Section: Introductionmentioning
confidence: 99%